Solid polymer electrolytes based on lithium bis(trifluoromethanesulfonyl)imide/poly(vinylidene fluoride -co-hexafluoropropylene) for safer rechargeable lithium-ion batteries - Gonçalves, Renato Ferreira (2019)
The increasing use of electronic portable systems and the consequent energy demand, leads to the need to improve energy storage systems. According to that and due to safety issues, high-performance non-flammable electrolytes and solid polymer electrolytes (SPE) are needed.SPE containing different amounts of lithium bis(trifluoromethanesulfonyl) imide (LiTFSI) into a poly(vinylidene fluoride-co-hexafluoropropylene), PVDF-HFP, polymer matrix have been prepared by solvent casting. The addition of LiTFSI into PVDF-HFP allows to tailor thermal, mechanical and electrical properties of the composite.In particular, the ionic conductivity of the composites increases with LiTFSI content, the best ionic conductivities of 0.0011 mS/cmat 25 degrees C and 0.23 mS/cmat 90 degrees C were obtained for the PVDF-HFP/LiTFSI composites with 80 wt % of LiTFSI.This solid electrolyte allows the fabrication of Li metallic/SPE/C-LiFePO4 half-cells with a discharge capacity of 51.2 mAh/ g at C/20. Further, theoretical simulations show that the discharge capacity value depends on the lithium concentration and percentage of free ions and is independent of the solid polymer electrolyte thickness. On the other hand, the voltage plateau depends on the SPE thickness. Thus, a solid electrolyte is presented for the next generation of safer solid-state batteries.